Comparison of Serum Levels of Vitamin D in Patients With and Without Acute Coronary Syndrome - Hassanzadeh Makoui, Reza; Soltannejad Dizaji, Mahsa; Khederlou, Hamid (International Journal of Cardiovascular Practice, 2018)
Introduction: Coronary artery disease is one of the most common causes of mortality around the world. The association between vitamin D deficiency and the incidence  of diseases, such as hypertension, diabetes, and metabolic syndrome, has been demonstrated previously. There have been studies concerning the relationship between vitamin D deficiency and cardiovascular diseases, which have shown different results. Therefore, this study aimed at determining the association between serum levels of vitamin D and acute coronary syndrome.Methods: In this case-control study, serum levels of vitamin D were compared between 50 patients with acute coronary syndrome and 50 individuals without this syndrome. A checklist, including demographic data of patients, comorbidities, vitamin D levels, lipid profiles, Electrocardiogram (ECG) changes and echocardiography results, was completed during hospitalization.Results: Mean age in the case and control group was 63.26 ± 10.76 and 61.22 ± 10.71 years, respectively. The prevalence of diabetes and high blood pressure in the case group was 32% and 54% versus 10% and 8% in the control group, respectively. Overall, 70% and 18% of subjects were smokers in the control and case groups, respectively. Mean concentration of vitamin D in serum was 20.63 ± 13.90 ng/mL, which was significantly lower than the control group with a mean concentration of 29.54 ± 16.8 ng/mL (P-Value = 0.002). Finally, it was shown that for every one unit increase in vitamin D levels, the risk of acute coronary syndrome was reduced by 7% (P-Value = 0.005).Conclusions: The results of this study showed that the serum levels of vitamin D were significantly lower in patients with acute coronary syndrome compared to those without this disease.